Molten salt electrosynthesis of Cr2GeC nanoparticles as anode materials for lithium-ion batteries - Pang, Zhongya; Tian, Feng; Xiong, Xiaolu; Li, Jinjian; Zhang, Xueqiang; Chen, Shun; Wang, Fei; Li, Guangshi; Wang, Shujuan; Yu, Xing; Xu, Qian; Lu, Xionggang; et al. (Frontiers in Chemistry, 2023)
The two-dimensional MAX phases with composition diversity enables them as promising functional materials for electrochemical energy storage. Herein we report the facile preparation of Cr2GeC MAX phase from oxides/C precursors by molten salt electrolysis method at a moderate temperature of 700 oC. The electrosynthesis mechanism has been systematically investigated, and the results show that the synthesis of Cr2GeC MAX phase involves the electro-separation and in-situ alloying processes. The as-prepared Cr2GeC MAX phase with typical layered structure shows uniform morphology of nanoparticles. As a proof of concept, Cr2GeC nanoparticles is investigated as anode materials for lithium-ion batteries, which delivers a good capacity of 177.4 mAh g−1 at 0.2 C and excellent cycling performance. The lithium-storage mechanism of Cr2GeC MAX phase has been discussed based on density functional theory (DFT) calculations. This study may provide important support and complement for the tailored electrosynthesis of MAX phases towards high-performance energy storage applications.